Cancer Therapy: Dendritic Platinum–Copper Alloy Nanoparticles as Theranostic Agents for Multimodal Imaging and Combined Chemophotothermal Therapy (Adv. Funct. Mater. 33/2016). (September 2016) - Zhou, Zhengjie; Hu, Kewen; Ma, Rui; Yan, Yang; Ni, Bing; Zhang, Yunjiao; Wen, Longping; Zhang, Qiang; Cheng, Yiyun
Abstract : On page 5971, Q. Zhang, Y. Cheng, and co‐workers describe a dendritic platinum‐copper alloy nanoparticle (DPCN) inherently possessing multimodal image modalities, photothermal effect, drug loading capability, and responsive release behaviors. Efficient tumor ablation in DPCN‐mediated chemo‐photothermal therapy proves the potential of this approach for cancer therapy.